Karakterisasi Dinamika Populasi Mikroba pada Cairan Hasil Samping Fermentasi Kopi Arabika (Coffea arabica L.) - Hakim, Syahirman; DEFRI, IFWARISAN; irwansyah, Irwansyah; Khusni, Jabar; Desparita, Naya; Baihaqi, Baihaqi (Universitas Teuku Umar, 2025)
Fermentation is a crucial stage in Arabica coffee processing involving the activity of various microorganisms. This process not only affects coffee bean quality but also generates a liquid by-product with potential application as a microbe-based probiotic beverage in agroindustry. This study aimed to characterize the dynamics of microbial populations in the liquid by-product of Arabica coffee fermentation during the fermentation process. Liquid samples were collected at fermentation intervals of 5, 10, and 15 days. Analyses included total microbial enumeration using the Total Plate Count (TPC) method, isolation of lactic acid bacteria on de Man, Rogosa, and Sharpe Agar (MRSA), and Gram staining tests. The results showed a significant increase in microbial populations with increasing fermentation time. Total microbial counts reached 3.09 × 108 CFU/mL on day 5, increased to 9.20 × 108 CFU/mL on day 10, and peaked at 3.09 × 1010 CFU/mL on day 15. Microscopic observations revealed Gram-positive rod-shaped isolates at all fermentation stages, with cell density increasing from day 5 to day 15. The morphological characteristics of the isolates were consistent with the genus Lactobacillus, indicating that fermentation duration is a key factor influencing microbial population dynamics. These findings highlight the important role of microorganisms in coffee fermentation and demonstrate the potential of fermentation by-products as a source of functional microbes for agroindustrial and biotechnological applications.